The association between health information exchange and measures of patient satisfaction - Vest, J.R.; Miller, T.R. (Applied Clinical Informatics, 2011)
Objective: Health information exchange (HIE) is the interorganizational sharing of patient information and is one of many health information technology initiatives expected to transform the U.S. healthcare system. Two outcomes expected to be improved by HIE are patient-provider communication and patient satisfaction . This analysis examined the relationship between the level of HIE engagement and these two factors in a sample of U.S. hospitals.Methods: Independent variables came from existing secondary sources and the dependent measures were from the Hospital Consumer Assessment of Healthcare Providers and Systems. The analysis included 3,278 hospitals. Using ordinary least squares regression, implemented HIE was positively associated with the percentage of patients reporting nurses communicated well and higher satisfaction. Due to the potential for selection bias, results were further explored using a propensity score analysis.Results: Hospitals that had adopted HIE, but not yet implemented saw no benefits. Hospitals’ level of HIE was not associated with the percentage of patients reporting doctors communicated well. According to propensity score corrected estimates, implemented HIE was associated with the percentage of patients who reported nurses always communicated well and who would definitely recommend the hospital.Conclusion: Few studies have examined the impact of HIE at the organizational level. This examination provides some evidence that hospitals engaging in HIE are associated with higher patient satisfaction.
Keywords: Hospitals; data sharing; healthcare quality assessment; propensity score; patient satisfaction; communication